New poly(ether urethane)s based on lignin derived aromatic chemicals via A-B monomer approach: synthesis and characterization - Kuhire, Sachin S.; Avadhani, C. V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2015)
{omega-Hydroxyalkyleneoxy benzoyl azides were synthesized starting from lignin-derived phenolic acids (vanillic acid and syringic acid) and omega-haloalkanols (6-chlorohexanol and 11-bromoundecanol). These bio-derived A-B monomers were self-polycondensed to afford poly(ether urethane)s which exhibited reasonably high molecular weights (eta(inh) = 0.41-0.69 dL g(-1), and M-n
Keywords: A-B type monomer; Poly(ether urethane)s; Renewable resources; Self-polycondensation